Towards the Design of a Networked Social Services Media Model to Promote Democratic Community Participation in South African Schools - Monson, Michael Leslie (Department of Information Systems, 2019)
The belief that society benefits from the adoption of democratic practices and a desire to improve schooling in South Africa, motivate this research. The social objective of the research is therefore to determine what are the causes of the persistent failure of the South African schooling system and to what extent community participation may serve to resolve them. The technological objective is to determine the feasibility of utilising social media for addressing social problems through enabling participative democracy. The potential for community participation in South African schools is therefore viewed through the lens of Internet enabled participative democracy. A design science-inspired research framework is devised in a qualitative study adopting a critical interpretevist epistemology. The study entails three phases applying a mixing of methods to perform critical research, context-based evaluation and critical interpretive evaluation. The first phase reveals the fundamental problems impacting the schooling education system in South Africa and determines that the underlying cause for their persistence lies in a systemic problem of conflicting legislation and policies caused by ideological differences within the ruling tripartite alliance. It further identifies through critical inference, specific practices by school communities which could improve the education system by participative, democratic action. The second phase evaluates the capacity for selected, popularly used social media artefacts to serve as communication and collaboration tools, in the schooling context, to enable community participation. These are found to be inadequate. The third phase is an evaluation of the technologies capable of facilitating activities required to achieve democratic participation of communities in schools and results in the description of an artefact that could enable a “networked social service media” system. The paper substantiates the notion that an appropriately designed, Internet enabled social media artefact, can promote the participation of communities in schools in South Africa.